Using the branding TXM methodology in the design process of the “Future of the Present” project (DAPesquisa, 2024)
The main goaI of interaction design is to develop products with application usability involving the users. The objective of this research was to evaluate the application of Branding TXM methodology steps in the Interaction design process of the project - "Present’s Future:  Space for observation, analysis and interpretation of signs" (FPlab). This methodology provides the participation of the management and the project team, as well as the users, considering their experience and interface with the products. In the case study limits, qualitative, exploratory and descriptive methods of research were used. The results indicated that the brand re-design was made and other things were met, like the results of SWOT analysis, confirming that the methodology of the objectives have been achieved.
Keywords: USING THE BRANDING TXM METHODOLOGY IN THE DESIGN PROCESS OF THE “FUTURE OF THE PRESENT” PROJECT